Unveiling innovation-driven UX. (21st April 2023) - Ferreira, Deller James; Nogueira, Tiago do Carmo
Recently, a number of studies appeared that approached user experience factors and relationships among them. However, there is room to unveil user experience factors contextualised in innovation. A critical challenge highlighted in prior research is to study the relationships between coolness and emotional factors, and also between surpassing challenges and emotional factors. Thus, with the purpose to better understand innovation-driven user experience on websites, this work empirically tests and compares data collected from 357 users. Our findings provide evidence that coolness is a factor most commonly found in innovative websites than in non-innovative websites. Also, we revealed that when users have overcome challenges in an innovative website, there is an association between coolness and positive emotions.